Pengaruh Pemberian Ekstrak Daun Paku (Diplazium esculentum) terhadap Gambaran Histopatologik Aorta Tikus Wistar (Rattus norvegicus) yang diinduksi Diet Tinggi Lemak - Jeremy Elim Janilauren Pantouw; Carla Felly Kairupan; Nur Anindhita Kurniawaty Wijaya (Pusat riset dan Inovasi Nasional, 2026)
Atherosclerosis, as the leading cause of cardiovascular disease, can be triggered by a high-fat diet that causes hyperlipidemia. Fern leaves (Diplazium esculentum) contain various bioactive compounds (alkaloids, phenols, flavonoids, terpenoids) with antioxidant and anti-inflammatory potential, which are suspected to inhibit the formation of atherosclerotic lesions. This study aims to determine the effect of administering fern leaf extract on the histopathological features of the aorta in Wistar rats induced by a high-fat diet. This laboratory experimental study used 25 male Wistar rats divided into five groups: (A) normal control, (B) negative control (high-fat diet), (C) positive control (high-fat diet + simvastatin), (D) treatment I (high-fat diet + fern leaf extract 600 mg/kgBW), and (E) treatment II (high-fat diet + fern leaf extract 1200 mg/kgBW). The treatment was administered for 21 days. On the 22nd day, the aorta was taken and processed into histopathological preparations using Hematoxylin-Eosin (H&E) staining. The number of foam cells was counted at 400x magnification. Data were analyzed using the One-Way ANOVA test followed by the Tukey test. There were differences in the number of foam cells between groups. The post-hoc test showed a significant difference between group B (high-fat diet) and all other groups (p<0.001). There was no significant difference between group E (extract 1200 mg/kgBW) and group C (simvastatin) (p=0.783), nor between group D (extract 600 mg/kgBW) and group C (p=0.075). Fern leaf extract (Diplazium esculentum) is able to reduce the number of foam cells in the aorta of Wistar rats induced by a high-fat diet.